2019
DOI: 10.24925/turjaf.v7i12.2054-2061.2730
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Nutritional and Medicinal Values of Edible Wild and Cultivated Pleurotus ostreatus

Abstract: Because of its high nutritional value and pharmaceutical effects, oyster mushroom (Pleurotus ostreatus (Jacq. ex Fr.) P. Kumm.) is collected from nature and cultivated in large scale. This therapeutic mushroom is consumed as a functional food or food additive in soups, cereal and dairy products, and commercially used in nutraceuticals and dietary supplements. The mycochemicals including polysaccharides (crude fiber and β-glucans), essential amino acids, ergothioneine, peptides, (glyco)proteins, lectins, phenol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…Pleurotus genus has a high content of crude fiber (10.2%), as well as C. comatus (12.5%), and ß-glucans (25.9%); in particular, the highest amount of ß-glucans is found in P. ostreatus (up to 50%) (Tsai et al 2007;Corrêa et al 2016;Carrasco-Gonzalez et al 2017;Bulam et al 2019). This makes this genus one of the main and most interesting sources of ß-glucans, including pleuran, currently commercialized as a natural immunostimulant (Imunoglukan P4HÒ) due to its bioactivity (Carrasco-González et al 2017; Reis et al 2017;Golak-Siwulska et al 2018;Bulam et al 2019). On the contrary, the chitin level is significantly higher in A. bisporus than in P. ostreatus (Atila et al 2017).…”
Section: Nutritional Value Of Mushroomsmentioning
confidence: 99%
See 1 more Smart Citation
“…Pleurotus genus has a high content of crude fiber (10.2%), as well as C. comatus (12.5%), and ß-glucans (25.9%); in particular, the highest amount of ß-glucans is found in P. ostreatus (up to 50%) (Tsai et al 2007;Corrêa et al 2016;Carrasco-Gonzalez et al 2017;Bulam et al 2019). This makes this genus one of the main and most interesting sources of ß-glucans, including pleuran, currently commercialized as a natural immunostimulant (Imunoglukan P4HÒ) due to its bioactivity (Carrasco-González et al 2017; Reis et al 2017;Golak-Siwulska et al 2018;Bulam et al 2019). On the contrary, the chitin level is significantly higher in A. bisporus than in P. ostreatus (Atila et al 2017).…”
Section: Nutritional Value Of Mushroomsmentioning
confidence: 99%
“…Excellent protein content was found by Srikram and Supapvanich (2016) in R. cyanoxantha (49.20%, while it was 29.50% in R. virescens), by Ayaz et al (2011) in B. edulis (32.50 g/100 g dw) and a good one by Xu et al (2019) in L. deliciosus (17.19 g/100 g dw), rather low (4.22%), instead, in M. procera. Recent studies have shown as P. ostreatus (protein content 23%) meets the nutritional requirements for all essential amino acids, or even doubles or triples for some of them (Corrêa et al 2016;Carrasco-González et al 2017;Bulam et al 2019), and that A. bisporus has significant amounts of numerous essential and nonessential amino acids, with an overall protein content of 29.14% (Kakon et al 2012;Atila et al 2017). Also relevant is the fact that mushrooms are the major food source of ergothioneine, especially B. edulis, and some species also of glutathione (mainly C. aegerita among the national mushrooms, followed by B. edulis and P. ostreatus), amino acid compounds that are important antioxidants (Kalaras et al 2017).…”
Section: Nutritional Value Of Mushroomsmentioning
confidence: 99%
“…Pleurotus spp. is pharmaceutical mushrooms as antiviral, antitumor, antibiotic, antibacterial, hypercholesterolemia, and immunomodulating agent 10 .…”
Section: Introductionmentioning
confidence: 99%
“…They have cultivated for long years thanks to higher nutrients such as minerals, protein, amino acid, vitamins and fibres and also low in calories. Furthermore, mushrooms also contain antioxidant as phenolic, anthocyanin, enzymes, glucans which are extremely beneficial for human health (Kozarski et al, 2015;Taşkın et al, 2015;Bulam et al, 2019). They can consume as both fresh and dried.…”
Section: Introductionmentioning
confidence: 99%